(untitled) (Scientific journal of the Fergana State University, 2024)
This article talks about the Persian words used by the poet in Alisher Navoi’s work "Saddi Iskandarii", their synonyms, and the synonymous line. The scientific opinions of world linguists about synonyms are presented. The lexical meanings of the Persian synonyms in the work, based on the comments in Persian-Tajik dictionaries, comparison with the comments in other sources, and the lexical meanings of the Persian words in the annotated dictionary of Navoi’s works are presented. Explanations are given that synonyms should have the same amount of active semantic valence, should have the same grammatical category, and all synonyms in one synonymic line should be synonyms of each other. The lexical and semantic meanings of the Persian words mentioned in the article are explained.